Pricing the Equity-Based Financing of Mudharabah: Insights into its Drivers - Nazhatul Majalis; Ratna Mulyany; Zata Hulwani Zuhri (IQTISHADIA, 2021)
This study investigates the factors that influence the pricing of mudharabah financing as offered by Islamic Banks in Indonesia. Specifically, this study examines whether the operational cost to operating income (BOPO), risk factor and spread significantly influences the pricing of mudharabah financing. This study uses a quantitative method based on secondary data derived from the Islamic banks' financial statements for the period of  2014-2018. Purposive sampling is utilized, with the total 9 Islamic Commercial Banks being the samples that meet the criteria, resulting in 45 units of analysis for five years observation. This study uncovers that all of the three independent variables affect the dependent variable simultaneously. From the partial results, only two variables that affect the pricing of mudharabah financing, i.e. risk factors and spread. Meanwhile BOPO was found to have no association with the pricing of mudharabah financing. This study implies that pricing of mudharabah financing may be largely dependent of the risk factors and spread rather than the consideration on the operational cost to the operational income.